Margarita, How Beautiful the Sea: a Reflection on the Binary Construction Hegemony Versus Subordination - Méndez Sánchez, Diana Verónica (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This reflection article studies the work Margarita, está linda la mar (1998) by Nicaraguan writer Sergio Ramírez in the light of his relation with the context (postcolonial theory). From this point of view, an analysis in the dichotomous hegemony versus subordinating is proposed, where colonial prints are revealed from hegemonic projects. So, on the one hand it is demonstrated the hegemonic presence —politic and military— through the comparison of the two historical scenarios represented, as a consequence of the military intervention on the part of the national and foreign military forces that represented the control and the repression of a whole country and in the other hand the reflections around the condition of subordinating seen as an expression and opposing party  of the embedded and integrated  domination of the oppressed individuals.